Association Between Social Engagement and Depression Severity Among the Elderly: A Community-Based Study - Darmawati, Irma; Trần Ngọc Thanh, Đặng; Laili Perdani, Agni; Wahdini, Ridha; Sintia Wardany, Nadia (Universitas Muhammadiyah Surakarta, 2026)
Depression in the elderly is a public health issue that is sometimes influenced by low social interaction, but community-based studies are still limited. This study aims to analyze how social engagement relates to depression severity among elderly. This study used cross sectional approach and recruited 56 elderly participants aged 60–72 years. Depression level measured by the 30 item Geriatric Depression Scale (GDS). Social engagement was assessed with the Lubben Social Network Scale (LSNS). Data were analyzed using descriptive statistics, Spearman correlation, and linear regression analysis. Participants averaged score are 13.70 on depression (SD=5.77) and 17.57 on social engagement (SD=2.79). We found a negative correlation: less social contact linked to higher depression level (r = –0.288, p = 0.031). Regression confirmed this pattern which social engagement predicted depression levels (B = –0.398, p = 0.002). Social engagement is important to reduce depressive sign and symptoms among the elderly. Community-based programs is needed to strengthen social support to improve mental health in elderly.